Systematic Literature Review: Penerapan Konstruktivisme Sosial dalam Pembelajaran melalui Pendekatan Realistic Mathematics Education (RME) berbasis Etnomatematika: Systematic Literature Review: Penerapan Konstruktivisme Sosial dalam Pembelajaran melalui Pendekatan Realistic Mathematics Education (RME) berbasis Etnomatematika - Mufti, Faiza Izzati (Jurnal Riset Pendidikan Matematika Jakarta, 2025)
With the problem of difficulty understanding mathematical ideas experienced by students, due to the abstract nature of ideas and their rarity in our everyday existence. Therefore, a social constructivist philosophical view emerged which emphasizes learning by building students' own knowledge based on their experiences which can be applied through Ethnomathematics-based Realistic Mathematics Education (RME) offering learning from authentic settings, namely through culture. This research tries to provide a literature review regarding the use of social constructivism in Ethnomathematics-based Realistic Mathematics Education (RME). Systematic Literature Review (SLR) is the research method chosen for this research. The data collection process includes collecting and analyzing every published article and book that discusses the philosophy of social constructivism and ethnomathematics-based RME. The journals used in this research are national and international journals indexed by SINTA and SCOPUS. Research findings show that ethnomathematics-based RME techniques can build mathematical concepts by utilizing the cultural context. Everyday existence occurs within a cultural framework. Learning with an ethnomathematics-based RME approach is effective because it can improve various types of mathematical abilities.